[C ii] Haloes in ALPINE galaxies: smoking-gun of galactic outflows?. Issue 3 (3rd January 2022) - Pizzati, E; Ferrara, A; Pallottini, A; Sommovigo, L; Kohandel, M; Carniani, S
ABSTRACT: ALMA observations have revealed that many high-redshift galaxies are surrounded by extended (10–15 kpc) [C ii] -emitting haloes that are not predicted by even the most advanced zoom-in simulations. Using a semi-analytical model, in a previous work we suggested that such haloes are produced by starburst-driven, catastrophically cooling outflows. Here, we further improve the model and compare its predictions with data from seven star-forming (10SFR/M_ yr^-1100 ) galaxies at z = 4–6, observed in the ALPINE survey. We find that (a) detected [C ii] haloes are a natural by-product of starburst-driven outflows; (b) the outflow mass loading factors are in the range 4 ≲ η ≲ 7, with higher η values for lower mass, lower star formation rate systems, and scale with stellar mass as η M_*^-0.43, consistently with the momentum-driven hypothesis. Our model suggests that outflows are widespread phenomena in high- z galaxies. However, in low-mass systems the halo extended [C ii] emission is likely too faint to be detected with the current levels of sensitivity.